Neuroleptic drugs in the treatment of tuberculosis: Minimal inhibitory concentrations of different phenothiazines against Mycobacterium tuberculosis. (May 2016) - Vesenbeckh, Silvan; Krieger, David; Bettermann, Gudrun; Schönfeld, Nicolas; Bauer, Torsten Thomas; Rüssmann, Holger; Mauch, Harald
Summary: Due to an increase of drug resistant TB, alternative drugs that are not currently listed in the WHO guidelines on MDR TB treatment are currently being evaluated. Our group tested 100 susceptible, 20 MDR and 2 XDR Mtb strains against the phenothiazine derivatives thioridazine, trifluoperazine and triflupromazine. MIC testing was performed on Middlebrook 7H10 agar and was defined as the lowest drug concentration that inhibits ≥99% of the bacterial population. We confirm very good in vitro activity of phenothiazines against Mycobacterium tuberculosis . In >77% of all strains MICs of ≤10 μg/ml were found.